A longitudinal study of changes in psychosocial well-being during orthognathic treatment - Alanko Outi; Tuomisto Martti T.; Peltomäki Timo; Tolvanen Mimmi; Soukka Tero; Svedström-Oristo Anna-Liisa (Churchill Livingstone, 2022)
The aim was to evaluate changes in the psychosocial well-being of orthognathic surgery patients (n = 22) during treatment and to compare results with those of adults not requiring orthognathic treatment (n = 22). Patient data were collected before treatment (T0), after the first orthodontic examination (T1), three times during treatment (T2–T4), and 1 year after surgery (T5). In this article, only data corresponding to patient stage T5 are reported for the control subjects. Participants filled in a structured diary and the modified version of the Secord and Jourard body image questionnaire, the Orthognathic Quality of Life Questionnaire, the Rosenberg Self-Esteem Scale, and the Acceptance and Action Questionnaire II. Moreover, patients filled in the Symptom Checklist-90. After the placement of orthodontic appliances (T2), orthognathic quality of life, self-esteem, and psychological flexibility were lower and psychiatric symptoms increased. Improvements were observed from T2 to T5 in orthognathic quality of life, body image, self-esteem, psychological flexibility, and psychiatric symptoms. Treatment resulted in improvements from T0 to T5 in orthognathic quality of life, body image, and psychiatric symptoms. At T5, patient psychosocial well-being was comparable to or even better than that of control subjects. Orthognathic treatment seems to support psychological well-being, but the range of individual variation is wide.